Physicochemical Properties of Household Water in Rambagh Colony, Purnea District, Bihar - Sah, Radha Keot; Kumar, Sanjeev (Journal of Discoveries in Applied and Natural Science, 2024)
Water quality is critical for public health and well-being. This study assesses the physicochemical properties of household water in Rambagh Colony, Purnea District, Bihar, to understand its safety and suitability for consumption. Parameters such as pH, turbidity, total dissolved solids (TDS), hardness, and the presence of contaminants were analyzed. Results indicate that the water quality in the area varies, with several parameters exceeding safe limits. This paper highlights the need for improved water management and treatment practices in the region.